Metode Point Kriging Untuk Estimasi Sumberdaya Bijih Besi (Fe) Menggunakan Data Assay (3D) Pada Daerah Tanjung Buli Kabupaten Halmahera Timur - Guskarnali Guskarnali (PROMINE, 2016)
This research was conducted in the area Tanjung Buli, East Halmahera regency. This area has ironore resources in the prospects for exploration to exploitation with data obtained using spaced borehole25meter. Point kriging method with software SGeMS (Standard Geostatistic Modeling software) usedfor assessing of iron ore resource with size of block model dimensions 41x23x205 and unit blocks25x25x1 (in meters). The results of the assessment point kriging method obtained estimated values ofFe and kriging variance value is then used for the classification of resources based on relative krigingstandard deviation (RKSD) as classification of resource measured, indicated, and inferred. The resultsof cross-validation of the assay data-Fe-Fe estimation data from point kriging method. The results ofresource assessment Fe of measured amounted to 3,081,125 tonnes, Indicated amounted to6,878,563 tonnes and Inferred amounted to 97,781,563 tonnes. The pattern of spread showed high Fecontent above 14.40% Fe dispersed randomly (varies) or local-local in units of small blocks.Correlation coefficient value showed of 0.89 so it has a strong correlation between the assay data-Fewith Fe estimation data.